(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the outcomes of laparoscopic seminal vesiculectomy in patients treated for hematospermia at the Center for Andrology and sexual medicine, Viet Duc University Hospital. Method: This retrospective descriptive case series analyzed 36 patients who underwent laparoscopic seminal vesiculectomy for hemospermia at the Center for Andrology and sexual medicine, from January 2021 to March 2024. Results: The average age was 51.4 ± 11.8 years. All patients have 2 or more children. Average surgery time was 188.3 ± 18.3 (min). Average hospital stay 8.7 ± 2.9 (days). Number of trocars used in each surgery: 28 patients (77.8%) used 4 trocars and 8 patients (22.2%) used 5 trocars. Complications during surgery: 3 patients (8.3%) (2 patients with bladder perforation and 1 patient with ureteral burn). No patient lost blood and needed blood transfusion during or after surgery. No patients had to be converted to open surgery. 2 patients (5.5%) had persistent hematuria after 1 month of re-examination. Pathological characteristics: chronic inflammation, congestion and bleeding of seminal vesicles 72.2% (26 patients), seminal vesicle Amyloid deposition disease 13.9% (5 patients), seminal vesicle cyst bleeding 8.3% (3 patients), malignant lymphoma Calculated 5.6% (2 patients). Median follow-up was 8 months (3-16). All patients no longer had hematospermia after surgery. 97.2% of patients were satisfied with the surgical results. Surgery did not affect the erectile function of the penis. Surgery reduced semen volume and sperm count. Conclusion: Laparoscopic seminal vesiculectomy is a safe and effective method for patients with hematospermia due to seminal vesicle bleeding. Surgery itself does not significantly affect erectile function. The volume of semen and amount of sperm are reduced that stem from surgery.